The Effectiveness of Social Media as a Medium for Islamic Da’wah in the Digital Era: A Systematic Literature Review - Aulia Rachmah (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose − The development of digital technology has changed the pattern of Islamic da'wah from a conventional approach to a more interactive and participatory social media-based da'wah. This research aims to examine the effectiveness of social media as a means of Islamic da'wah in the digital era. Method − Used is Systematic Literature Review (SLR) with PRISMA guidelines for 20 articles of reputable scientific journals published in the last ten years. Findings − The results of the study from 20 articles show that social media such as Instagram, TikTok, YouTube, and Facebook are effective in several fields of da'wah, namely the dissemination of Islamic information and education, the improvement of religious understanding and literacy, the formation of religious attitudes and behaviors, the expansion of the reach of da'wah, especially in the younger generation, and the increase of audience interaction and participation. The effectiveness is influenced by the quality of the content, the suitability of the platform, the interactive communication strategy, and the credibility of the preacher. The conclusion of this study emphasizes that social media can be an effective means of Islamic da'wah if it is managed strategically, ethically, and contextually and oriented towards the quality of the message and the religious impact of the audience.